Genetic interactions among vestigial, hairy, and Notch suggest a role of vestigial in the differentiation of epidermal and neural cells of the wing and haltere of Drosophila melanogaster. - Abu-Issa, R.; Cavicchi, S. (Journal of Neurogenetics, 1996)
In this paper we describe the results of genetic analysis of the vestigial locus by studying its interactions with hairy and Notch loci in Drosophila melanogaster. Different vestigial alleles in homo- and heterozygous combination with different hairy alleles show synergism in increasing both cell death and formation of ectopic bristles and produce ectopic veins. Interactions between N and vg also show synergism in increasing cell death and formation of ectopic bristles. Only synergism in cell death is seen between h and N. The interactions indicate that vg product plays a role in the differentiation of epidermal and neural cells of the wing disc by interacting with N and h products either directly or indirectly. Mechanisms of molecular interactions among the three loci are discussed.